Toxicity determination of the brown planthopper (Nilaparvata lugens) on paddy (Oryza sativa) towards selected insecticides / Siti Aisyah Sanusi - Sanusi, Siti Aisyah (Faculty of Plantation and Agrotechnology, 2018)
The Brown Planthopper (BPH) Nilaparvata lugens have been known to infest the various variety of paddy rice. This insect pest belongs to the order of Homoptera and the family of Delphacidae. BPH damage the paddy crops by directly feeding on phloem and indirectly by transmitting plant diseases such as stunting and wilting. Insecticides commonly used to kill BPH without recommended dose will affect animals and the environment. Insecticides have different action modes. Some insects will react to insecticides differently. It depends on the type of contact. Such insecticide contact by enters the body of insects and other types of insecticides enter the body through the insect tracheal system. Each insecticide has a different toxicity level to insect pest. The toxicity of insecticide is measured by the point at which 50% of the insect population is killed and known as Lethal Dose, (LD50) or Lethal Concentration (LC50). The LD50 is very important in order to determine the effectiveness of insecticides against BPH. Three selected insecticides which currently used by farmers were tested by using bioassay method. The insecticides were namely Fipronil 97.5%, Imidacloprid 99.9%, and Cypermethrin 94.3%, with five concentrations of each insecticide. Data of LD50 was analysed using special PROBIT PoloPlus Analysis. It provides estimates of median lethal dose of specified mortality levels (such as LD50, LD90, and LD95) which can be used for statistical comparison of each preparation with a standard. Fipronil 97.5% was the most toxic insecticides among these three selected insecticides used, with LD50 was 127.979 ng/g. Followed by Imidacloprid 99.9% was 283.062 ng/g. While the less toxic was Cypermetrin with the LD50 value was 441.395 ng/g. This study important to farmers when applying insecticides in recommended IPM program so that the insect do not built the resistance in the farm.